miR-1297 promotes cell proliferation by inhibiting RB1 in liver cancer - Liu, Chengyong (Oncol Lett, 2016)
Liver cancer is the one of the most common causes of cancer-associated mortality worldwide. MicroRNAs (miRNAs or miRs) are important in various types of cancer, including liver cancer. In the present study, with miRNA expression profile data obtained from the Gene Expression Omnibus database, three independent methods were used to investigate the miRNAs that are involved in liver carcinogenesis, including Fisher's exact test, t-test and Wilcoxon test. Five differentially expressed miRNAs were identified. Among them, miR-1297 drew specific attention. Target gene analysis and Ingenuity Pathway Analysis revealed its potential impact on cell death and cell cycle. Cell Counting Kit-8 proliferation assay indicated that the HepG2 cell proliferation was promoted by miR-1297, while miR-1297 inhibitor could significantly inhibit the proliferation of HepG2 cells. Luciferase assays confirmed that miR-1297 directly bound to the 3′-untranslated region of retinoblastoma (RB)1, and western blotting demonstrated that miR-1297 suppressed the expression of RB1 at the protein level. RB1 is involved in the regulation of the human cell cycle pathway. It is possible that miR-1297 contributes to the carcinogenesis of liver cancer via downregulation of the tumor-suppressor gene RB1. Our results suggest that miR-1297 may serve as a potential therapeutic target of liver cancer.